1995
DOI: 10.1111/j.1601-0825.1995.tb00172.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between elastase and lactoferrin in healthy, gingivitis and periodontitis sites

Abstract: OBJECTIVES: To compare the relative amounts of elastase (primary polymorphonuclear leucocyte granule constituent) and lactoferrin (secondary PMN granule constituent) in the gingival crevicular fluid (GCF) of healthy, gingivitis and periodontitis sites. DESIGN: This cross‐sectional study looked at the two GCF constituents in three categories of disease status within the same subject. MATERIALS AND METHODS: Patients with chronic adult periodontitis were screened and those exhibiting all three types of sites ie p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…In consequence, it could be speculated that lactoferrin acts by its antimicrobial activity and not by the inhibition of biofilm formation at this time. This interpretation of the current data is in agreement with the observation that the protein is strongly upregulated within external secretions during airway, gut, and periodontal inflammations 9,10,40‐42 . In addition, no significant association between lactoferrin levels and measures of health status or plaque accumulation could be found in humans 43 and animals, 44 an observation that may be indicative for the antimicrobial activity of lactoferrin.…”
Section: Discussionsupporting
confidence: 91%
“…In consequence, it could be speculated that lactoferrin acts by its antimicrobial activity and not by the inhibition of biofilm formation at this time. This interpretation of the current data is in agreement with the observation that the protein is strongly upregulated within external secretions during airway, gut, and periodontal inflammations 9,10,40‐42 . In addition, no significant association between lactoferrin levels and measures of health status or plaque accumulation could be found in humans 43 and animals, 44 an observation that may be indicative for the antimicrobial activity of lactoferrin.…”
Section: Discussionsupporting
confidence: 91%
“…British (Murray, Mooney, & Kinane, 1995) subjects, no differences between patients with periodontitis and controls were detected.…”
Section: Discussionmentioning
confidence: 82%
“…As regards the role of lactoferrin in periodontal disease (Fine, ), higher lactoferrin salivary levels were measured in Australian (Huynh et al., ), Indian (Yadav et al., ), Swedish (Glimvall, Wickstrom, & Jansson, ), Finnish (Suomalainen, Saxen, Vilja, & Tenovuo, ), Taiwanese (Tsai, Kao, & Chen, ; Wei et al., ), American (Fine, Furgang, & Beydouin, ), and British (Adonogianaki, Moughal, & Kinane, ) periodontitis patients with respect to healthy controls, while low lactoferrin level was found among Brazilian (Rocha Dde et al., ) and Chinese (Wu, Shu, Luo, Ge, & Xie, ) periodontitis patients. Finally, among Japanese (Ikuta et al., ), Swedish (Figueredo & Gustafsson, ), and British (Murray, Mooney, & Kinane, ) subjects, no differences between patients with periodontitis and controls were detected. Moreover, a study reported that high concentration of lactoferrin in gingival crevicular fluid significantly reduces after periodontal therapy (Yadav et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…However, these markers were elevated in periodontally diseased compared with healthy subjects. Earlier studies indicated a similarity in GCF protein concentration (Gustafsson, Asman, & Bergstrom, 1995) or elastase levels (Jin, Soder, Asman, & Bergstrom, 1995;Murray, Mooney, & Kinane, 1995) in sites with various degrees of disease in the same periodontitis patient. In accordance with our findings, a later study (Teles, Sakellari, Teles, et al, 2010) indicated that sites without clinical signs of disease in diseased subjects showed higher levels of several cytokines than healthy sites in healthy subjects.…”
Section: Discussionmentioning
confidence: 98%